2019
DOI: 10.1007/978-3-030-29374-1_15
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship Between Data Science and Circular Economy: An Enhanced CRISP-DM Process Model

Abstract: To date, data science and analytics have received much attention from organizations seeking to explore how to use their massive volumes of data to create value and accelerate the adoption of Circular Economy (CE) concepts. The correct utilization of analytics with circular strategies may enable a step change that goes beyond incremental efficiency gains towards a more sustainable and circular economy. However, the adoption of such smart circular strategies by the industry is lagging, and few studies have detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Thirdly, it is necessary to consider firm’s micro behavior from circular economy strategies. Especially, with the advent of the digital economy era, digital technologies are essential enables of the circular economy [ 49 , 50 ], and the effect of green credit guidelines on green technology innovation may show other heterogeneity characteristics. All of these limitations are the directions of our further study.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Thirdly, it is necessary to consider firm’s micro behavior from circular economy strategies. Especially, with the advent of the digital economy era, digital technologies are essential enables of the circular economy [ 49 , 50 ], and the effect of green credit guidelines on green technology innovation may show other heterogeneity characteristics. All of these limitations are the directions of our further study.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…This agrees with the so far limited research performed on digital perspective. Despite it being demonstrated that organizations can take advantage of their data understanding and preparation to align with overall business sustainability [24], the SDGs declaration shows a lack of attention to the critical role of ICTs in shaping contemporary development [25]. ICTs are not mentioned directly in any of the SDGs and are only mentioned in four of the 169 targets.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…The mass-production of the 20th century was carbon-intensive and extraction-based, raising central queries about the sense of the development [80]. Hence, aiming to dissociate economic activity from the consumption of limited resources, the concept of circular economy focused on recycling, effectiveness, and productivity, emerged along with the goal of preserving goods in operation for longer [81]. Additionally, ecological modernization theory suggests that sustained industrial progress, instead of unavoidably continuing to damage the atmosphere, provides the supreme choice of running away from the worldwide ecological challenge [82].…”
Section: Earlier Studies On the Impact Of Technological Innovation On Company Performancementioning
confidence: 99%